SEGMENTED CENTRALITIES: THE SHOPPING MALLS OF SAO JOSE DO RIO PRETO/SP - Lima, Luiz Henrique Mateus [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2016)
Becoming part of Brazilian cities between the 1960s and 1970s, the shopping malls have become common in the country over the years, representing a form of removal of the classes that have a higher purchasing power to maintain the distance the unwanted , that is, the classes living in a lower income and thus cannot afford to consume in consumer spaces with similar structure. In this article, we analyze the centrality generated from the four shopping malls-Riopreto Shopping, Plaza Avenida Shopping, Shopping Cidade Norte and Iguatemi Rio Preto - Sao Jose do Rio Preto/SP, seeking to reveal the links between geographical scales in production urban space, as well as understand the locational that guide the implementation of these projects in medium-sized cities in order to identify its relationship with socioeconomic segment that target and impacts including the intra-urban scale. With the first shopping mall was inaugurated in 1988, this development model boosted in Sao Jose do Rio Preto, the development of new downtowns in the city, attracting to its interior, consumers not only local, but also from other cities including neighboring states to Sao Paulo.
Keywords: Production of urban space; shopping malls; centrality; Sao Jose do Rio Preto/SP